Western psychology and eastern psycho-spirituality in dialogue: A comparative analysis of Freudian structural model of the psyche and Triguna model of the Bhagavad Gita - Mandal, Sudeb; Tiwari, Sandhya (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: This article attempts to examine the shared perspectives of Sanatan Psycho-spiritual theory and Freud’s psychoanalytic theory apropos of the construction of human personality. The objective of this article is to demonstrate how a theological text, composed approximately 5,000 years ago, articulates key concepts that exhibit remarkable parallels with modern psychological theories, which are grounded in empirical inquiry and theoretical speculation. By examining these intersections, this study aims to contribute to the development of an interdisciplinary framework, bridging ancient philosophical thought with contemporary psychological discourse and opening new avenues for scholarly exploration. Methods: By examining the concept of Tri-Guna alongside Freudian Structural Model of the Psyche, the study aims to foreground how Eastern and Western paradigms participating in a dialogue can offer complementary understandings of human psychology and psycho-spirituality. Findings: Operating from this perspective, this article uncovers the deeper philosophical and psychological underpinnings common to both Freudian and Satan Psycho-spiritual school of thought, focusing on the concepts of Tamas, Rajas, and Sattva, and their Western equivalents – Id, Ego, and Superego. Conclusion: The comparative analysis of the Bhagavad Gita’s concept of Tri-gunas and Freud’s structural model of the psyche reveals a shared perspective that human personality and behavior are fundamentally shaped by underlying biological constructs. This framework highlights the intricate entanglement of Determinism and Free Will within both schools of thought. Novelty/Originality of this article: By disentangling these connections, this paper proposes to offer new insights into how Eastern and Western thought systems converge in their understanding of human nature, mind and psyche and the pursuit of an equanimous-mind. The comparisons in this article shed light on the intricacy and entanglement between Determinism and Free Will, introducing new coordinates for dialogue between the Western model of the psyche and Eastern psycho-spirituality, fostering a discourse that will deepen our perspectives and contribute to the advancement of psychological scholarship.